1993
DOI: 10.1177/106342669300100204
|View full text |Cite
|
Sign up to set email alerts
|

When, How, and Why Educational Placement Decisions Are Made

Abstract: Students with emotional or behavioral disorders are frequently placed in restrictive settings, yet we have little knowledge or understanding of the decisions leading to these placements. We interviewed educators involved in decisions to place two students with emotional or behavioral disorders in a special regional day school program. We were particularly interested in information regarding the rationale, procedures, participants, and contexts of these placement decisions. In these cases we think that the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In addition, academic programming practices in these classrooms did not substantially differ from GE settings in any way that would benefit students with EBD. These data are consistent with prior research concluding that intervention practices for students with EBD are informal and ambiguous (Hallenbeck, Kauffman, & Lloyd, 1993;Jack et al, 1996). As previous studies have indicated, little was occurring in the classrooms to address the social, behavioral, or academic needs of the students.…”
Section: Class-wide Levelsupporting
confidence: 90%
“…In addition, academic programming practices in these classrooms did not substantially differ from GE settings in any way that would benefit students with EBD. These data are consistent with prior research concluding that intervention practices for students with EBD are informal and ambiguous (Hallenbeck, Kauffman, & Lloyd, 1993;Jack et al, 1996). As previous studies have indicated, little was occurring in the classrooms to address the social, behavioral, or academic needs of the students.…”
Section: Class-wide Levelsupporting
confidence: 90%
“…Teachers who may be most aware of student behavior in the school setting may not participate fully in placement decisions (Vacc et al, 1985). In addition, parents who are experts on their child's behavior at home and in the community may not be in attendance (Nyberg, 1990), and psychoeducational evaluation results are often underused (Hallenbeck et al, 1993). How an integrated system of care which prioritizes authentic family involvement and professional collaboration may impact these findings is of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…Youths with EBD may be served in general education classrooms with the support of classroom aides and mental health providers, yet statistics show that typically only 14.1% are placed in such settings (U.S. Department of Education, 1991). Instead, researchers have reported that youths with EBD are often segregated from the mainstream, placed more commonly outside of their home school districts and in residential facilities (Hallenbeck, Kauffman, & Lloyd, 1993).…”
mentioning
confidence: 99%
“…Research on the distribution of children with disabilities over the continuum of special education demonstrates that children with EBD are usually placed in educational settings of a more restrictive type (Cullinan, Epstein, & Sabornie, 1992; De Greef & Van Rijswijk, 2006; Denny, Gunter, Shores, & Campbell, 1995; Stoutjesdijk & Scholte, 2009) because EBD is considered the most challenging group of disabilities to be handled in regular education (regardless of whether additional support is available; Hallenbeck, Kauffman, & Lloyd, 1993; Kauffman & Landrum, 2009). A similar picture emerges when a comparison is made between children with EBD and children with other forms of disabilities, such as physical handicaps or learning disabilities (LD); in special education, children with EBD are more often placed in segregated classrooms or separated facilities (De Greef & Van Rijswijk, 2006; Epstein, Nelson, Polsgrove, Coutinho, & Quinn, 1993; Stephens & Lakin, 1995).…”
mentioning
confidence: 99%
“…Given the considerable efforts on the part of governments to offer children with disabilities the opportunity to be educated in regular schools, the question arises why the inclusion of children with EBD in these school settings is relatively limited. This is an important matter to address not only in light of children’s abilities and educational rights but also considering the findings that some children with EBD are being placed in more restrictive settings than strictly necessary (Epstein & Cullinan, 1994; Hallenbeck et al, 1993). Furthermore, once a placement decision has been made, few of these children change their educational setting (Buysse & Bailey, 1994).…”
mentioning
confidence: 99%